Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Perusahaan - Tya Destiani; Rina Maria Hendriyani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyze financial ratios with industry standard financial ratios used in the form of liquidity ratios, solvability ratios, and profitability ratios as a measuring tool for assessing the financial performance of Ltd Unilever Indonesia Plc. This research uses descriptive method with quantitative and qualitative approaches. The type of data used is secondary data, namely the financial statements of Ltd Unilever Indonesia Plc from 2016 to 2020. The data source used is internal data in the form of company profiles of Ltd Unilever Indonesia Plc. Data collection techniques in the form of library research and data analysis techniques in the form of descriptive. The results show that the financial performance of Ltd Unilever Indonesia Plc based on the liquidity ratio is not good because it is still below the financial ratio industry standard. Based on the solvability ratio, the company's financial performance is not good because the results are far below the industry standard of financial ratios. And based on the profitability ratios, the company's financial performance is very good because the results are above the industry standard financial ratios.